2020
DOI: 10.1007/s10620-020-06645-0
|View full text |Cite
|
Sign up to set email alerts
|

Infliximab Trough Levels Are Not Predictive of Relapse in Patients with IBD in Endoscopic Remission: A Multicenter Cohort Study

Abstract: Background-Therapeutic drug monitoring (TDM) is important in optimizing use of biologics in inflammatory bowel diseases (IBD). However, the role of proactive TDM during remission remains uncertain.Methods-This retrospective study included patients receiving infliximab (IFX) therapy at Massachusetts General Hospital (MGH) or Erasmus University Medical Center (EMC). All eligible patients had completed induction phase of IFX and were in clinical and endoscopic remission. Our primary outcome was clinical relapse w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…A comprehensive literature review and expert consensus statement recently added further clarity on the benefits of reactive and proactive TDM of biologic treatments, particularly anti-TNF (15). The topic still remains, however, largely debated (17).…”
Section: Discussionmentioning
confidence: 99%
“…A comprehensive literature review and expert consensus statement recently added further clarity on the benefits of reactive and proactive TDM of biologic treatments, particularly anti-TNF (15). The topic still remains, however, largely debated (17).…”
Section: Discussionmentioning
confidence: 99%
“…1 In contrast, even for anti-TNF therapy, there is less robust data on whether proactive TDM during quiescence beneficially impacts maintenance of sustained remission with recent studies demonstrating mixed results. 2 For the non-anti-TNF agents, the utility of TDM is less well-proven; there may be several reasons for this. First, the concept of fecal loss during active inflammation resulting in subtherapeutic trough concentration is less well proven for the non-TNF biologic agents.…”
Section: Strategies For Therapeutic Drug Monitoringmentioning
confidence: 99%
“…Moreover, and of concern, it is not possible to predict which patients will respond to which biologic therapies. Borren et al [5] reported stable infliximab concentrations over time in their patient population, albeit data were only available for a limited percentage of their patient population. The stability was posited to be due to less fecal loss of drug in quiescent disease.…”
mentioning
confidence: 97%
“…The need to optimize a level when someone is in remission, however, remains unclear. The study by Borren et al [5] suggests that this level is likely to remain stable and does not predict the risk of flaring. In fact, their study showed no difference in trough levels in those who relapsed versus those who did not (7.5 μg/mL ± 3.7 μg/mL vs. 8.1 μg/mL ± 7.9 μg/mL, p = 0.815) even though levels were typically above the target 5 μg/mL [5].…”
mentioning
confidence: 99%
See 1 more Smart Citation